2018
DOI: 10.3762/bjoc.14.84
|View full text |Cite
|
Sign up to set email alerts
|

Cross-coupling of dissimilar ketone enolates via enolonium species to afford non-symmetrical 1,4-diketones

Abstract: Due to their closely matched reactivity, the coupling of two dissimilar ketone enolates to form a 1,4-diketone remains a challenge in organic synthesis. We herein report that umpolung of a ketone trimethylsilyl enol ether (1 equiv) to form a discrete enolonium species, followed by addition of as little as 1.2–1.4 equivalents of a second trimethylsilyl enol ether, provides an attractive solution to this problem. A wide array of enolates may be used to form the 1,4-diketone products in 38 to 74% yield. Due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 34 publications
(31 reference statements)
0
19
0
Order By: Relevance
“…This highly electrophilic intermediate can react with a variety of different nucleophiles. Such oxidations are often promoted by acids or less frequently by bases, with enol ethers or active methylene compounds being commonly employed.…”
Section: Methodsmentioning
confidence: 99%
“…This highly electrophilic intermediate can react with a variety of different nucleophiles. Such oxidations are often promoted by acids or less frequently by bases, with enol ethers or active methylene compounds being commonly employed.…”
Section: Methodsmentioning
confidence: 99%
“…The α‐functionalization of certain ketones through oxidative umpolung with iodine(III) was pioneered already in the 1960s, has been extensively investigated in the 1980s, and gained further attention in more recent years . It is believed that the reaction involves an enolonium species (compound 8 , Scheme a) .…”
Section: Methodsmentioning
confidence: 99%
“…[24][25][26][27][28][29] The a-functionalization of certain ketones through oxidative umpolung with iodine(III) was pioneered already in the 1960s, [30,31] has been extensively investigated in the 1980s, [32][33][34][35][36] and gained further attention in more recent years. [37][38][39][40][41] It is believed that the reaction involves an enolonium species (compound 8, Scheme 1 a). [42,43] This highly electrophilic intermediate can react with a variety of different nucleophiles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to 1,4‐dicarbonyls in general, the synthesis of 1,4‐diketones poses a greater challenge, often requiring use of an excess of one coupling partner and/or significant pre‐functionalisation of substrates to achieve the desired heterocoupling. Reported methods include oxidative homocoupling [23–27] or heterocoupling of ketone enolates, [7,24,28–34,35,36] alkylation of enolates, [9,14,37–42] alkylation of acyl anion equivalents [43–47] or acyl radicals, [11,48] acylation of homoenolate equivalents, [12,13,49–52] or multicomponent strategies [53,54] . Only a subset of methods have been reported that tolerate aliphatic substrates for both reaction partners: addition of silyl enolates to oxyallyl zwitterions [10] and the aldehyde umpolung‐based Stetter reaction [4,5,45,55] …”
Section: Figurementioning
confidence: 99%